The Third Space: Exploring Identity Negotiation and Formation in Abdulrazak Gurnah’s Afterlives - Chigbu, Andrew Chigbu; Caroline Olubunmi Nwaka; Greg Omeje; Eze Onyinyechi Sophia (CINEFORUM, 2026)
Critical analyses of Gurnah’s Afterlives have centred on its treatment of colonial violence, trauma, memory, displacement, migration and environmental concerns. However, this paper examines the concept of the third space and its influence on identity development. Using postcolonial literary theory, particularly Bhabha’s idea of the third space, and the close reading method, it demonstrates that identity is continually negotiated at the complex intersections of language, culture, history, and the human psyche. The key argument is that these overlapping spaces depict identity as fluid, relational, and constantly evolving. The paper concludes that Gurnah’s novel transforms Bhabha’s concept into a tangible human experience, illustrating that postcolonial identity involves an ongoing negotiation of power and belonging, history and hope, thereby emphasising how literature reflects human resilience, adaptation, and agency.